Dynamic group key management scheme for clustered wireless sensor networks. (14th September 2020) - Saraswathi, R. Vijaya; Sree, L. Padma; Anuradha, K.
A Group Key Management is a technique to establish shared group key, between the cluster head and sensor nodes for multiple sessions in a clustered network environment. The common use of this established group key (also termed as conference key) is to permit users to encrypt and decrypt a particular broadcast message that is meant for the total user group. In this work, we propose a cluster based dynamic group key management protocol that is based on public key cryptography. Cluster head initiates establishment of group key to the sensor nodes efficiently and achieves secure communication. Later, the computation of the common group key is performed by each sensor node. Group members have functionality to join and leave from particular communication along with this, other nodes, equal to threshold compute new conference key without involvement of cluster head. The proposed protocol is investigated in terms of security and complexity analysis using network simulator (NS-2).